Foreign policy analysis new approaches - Alden, Chris (Routledge, 2012)
This exciting new book aims to re-invigorate the conversation between foreign policy analysis and international relations. It opens up the discussion, situating existing debates in foreign policy in relation to contemporary concerns in international relations, and provide a concise and accessible account of key areas in foreign policy analysis that are often ignored. Focusing on how the process of foreign policy decision making affects the conduct of states in the international system, and analysing the relationship between policy, agency and actors, the work examines: - foreign policy and bureaucracies - fomestic sources of foreign policy - foreign policy and the state - foreign policy and globalization - foreign policy and change This work builds on and expands the theoretical canvas of foreign policy analysis, shaping its ongoing dialogue with international relations and offering an important introduction to the field. It is essential reading for all students of foreign policy and international relations.